2004
DOI: 10.1128/mcb.24.15.6701-6709.2004
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 Is Required for Common-Fragile-Site Stability via Its G2/M Checkpoint Function

Abstract: Common fragile sites are loci that form chromosome gaps or breaks when DNA synthesis is partially inhibited. Fragile sites are prone to deletions, translocations, and other rearrangements that can cause the inactivation of associated tumor suppressor genes in cancer cells. It was previously shown that ATR is critical to fragile-site stability and that ATR-deficient cells have greatly elevated fragile-site expression (A. M. Casper, P. Nghiem, M. F. Arlt, and T. W. Glover, Cell 111:779-789, 2002). Here we demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(88 citation statements)
references
References 40 publications
2
86
0
Order By: Relevance
“…Recently, it has been shown that BRCA1 is required for common fragile-site stability. Cells lacking BRCA1 show an increased expression of specific common fragile sites (Arlt et al, 2004). This provides further evidence that cells lacking BRCA1 are likely to be prone to genomic alterations that can lead to deletion of associated genes and this consequently could promote tumourigenesis.…”
Section: Discussionmentioning
confidence: 74%
“…Recently, it has been shown that BRCA1 is required for common fragile-site stability. Cells lacking BRCA1 show an increased expression of specific common fragile sites (Arlt et al, 2004). This provides further evidence that cells lacking BRCA1 are likely to be prone to genomic alterations that can lead to deletion of associated genes and this consequently could promote tumourigenesis.…”
Section: Discussionmentioning
confidence: 74%
“…This shift in tumor spectrum could be due to increased genomic instability stemming from telomere replication defects, an inability to engage in HDR-mediated repair, or alterations in gene transcription involved in tumorigenesis. Common fragile sites are vulnerable to DNA insertions and deletions, promoting an unstable genome that contributes to the formation of some human cancers [39,42]. We speculate that defects in telomere replication in the absence of mIno80 might lead to similar increases in genomic instability to promote tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Telomeres resemble common fragile sites, difficult-to-replicate regions in the genome that, under conditions of replication stress, generate DSBs due to fork stalling [38][39][40][41]. Common fragile sites are vulnerable to DNA insertions and deletions, promoting genomic instability [39,42].…”
Section: Defects In Ssdna Formation and Telomere Replication In Mino8mentioning
confidence: 99%
“…45 Beside its role in sister chromatid cohesion, SMC1 is phosphorylated in an ATRdependent manner under conditions of replication stress and may contribute to the activation of the S-phase checkpoint after aphidicolin exposure, possibly allowing error-free resumption of DNA replication. 32,44 The observation that cells lacking BRCA1 show elevated levels of breakage at CFS after aphidicolin treatment, 33 represents, however, an interesting exception. Indeed, even though there is evidence that BRCA1 is phosphorylated by ATR in response to fork stalling, 46 its role in preventing breakage at CFS has been claimed not to be related to the S-phase checkpoint but rather to the G 2 /M checkpoint control regulating the onset of mitosis.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…As a logical consequence of the previous findings and strengthening their consistency, other components of the ATR-dependent checkpoint were found to influence the stability of fragile sites. Among them are several ATR substrates or mediator proteins: CHK1, 4 HUS1, 30 Claspin, 31 SMC1 32 and BRCA1 33 ( Table 1).…”
Section: Features Of Common Fragile Sites and Factorsmentioning
confidence: 99%